An event-triggered smart sensor network architecture - Erico Meneses Leão (2007)
A smart transducer is the integration of a sensor/actuator element, a processing unit and a network interface. Smart sensor networks are composed of smart transducer nodes interconnected through a communication network. This paper proposes a new architecture for smart sensor networks, that is driven by events (asynchronous data). The events are derived from a data compression algorithm embedded in the smart sensor, which compresses data from the sensor. The proposed architecture also provides configuration and monitoring data to manage the distributed system.